Demanda físico-operacional, salud y condiciones de trabajo entre policías y bomberos en Brasil y Portugal (Physical-operational demand, health and working conditions between tactical personnel in Brazil and Portugal) - Caetano, Hallyne Bergamini Silva; Fermino, Rogério César; Caetano, Cristiano Israel; Bocalini, Danilo S.; Paulo, Anderson (Retos, 2024)
Objetivos: Comparar las demandas físicas y operativas, la salud y las condiciones de trabajo entre los profesionales de la seguridad pública en Paraná y Portugal. Métodos: En 2020 se realizó un estudio con enfoque cuantitativo y diseño transversal en el que participaron 645 policías militares (PM) y 152 bomberos (BM) de Brasil y 1.154 de la Guardia Nacional Republicana (GNR) de Portugal. Las variables se evaluaron con el Cuestionario de desempeño y salud militar (QSPM) a través de Google Forms. Los datos se analizaron mediante la prueba de chi-cuadrado para la proporción (c2). Resultados: En cuanto a la demanda físico-operacional hubo asociación significativa en 15 de los 16 ítems cuestionados. Las mayores inconformidades (p < 0,001) fueron: “Disparar un arma de fuego” y “Entrar a un pantano o río para buscar o perseguir a alguien”. En cuanto a las condiciones de salud, hubo asociación significativa para los seis ítems cuestionados. El mayor desacuerdo se presentó en relación al nivel de estrés, considerado alto en el 46% de los BM, el 38% de los PM y el 35% de los GNR. El dolor lumbar estuvo presente en el 51% de BM, el 44% de PM y el 39% de GNR. Respecto a las condiciones de trabajo, también hubo asociación significativa para los 6 ítems encuestados. El mayor desacuerdo se produjo en relación con el lugar de trabajo, que fue considerado malo por el 33% de GNR, el 26% de BM y el 18% de PM. Además, el salario fue considerado malo por el 87% de GNR, el 74% de BM y el 65% de PM. Conclusiones: Aunque la GNR lleva a cabo actividades tanto de seguridad pública como de defensa social, se encontraron desacuerdos en varios puntos de la investigación en comparación con el PM y el BM. Los resultados obtenidos son una rica fuente de información para gestores e investigadores en el área de seguridad pública.Palabras clave: Sanidad Militar. Estrés profesional. Lumbalgia. Dormir. Jornada laboral.Abstract. Aims: To compare the physical-operational demands, health, and working conditions between public security professionals in Paraná and Portugal using the Health and Military Performance Questionnaire instrument (QSPM). Methods: A descriptive and sectional study was carried out with a sample of 645 military police officers and 152 firefighters from the State of Paraná, and 1,154 guards from Portugal. The Brazilian QSPM underwent a cross-cultural adaptation, and a link to the Google Forms platform was sent by email to all professionals. The results were stratified into policemen vs. firefighters vs. guards for the descriptive and inferential analysis. Results: Regarding physical-operational demand, the Chi-Square test (2) revealed a significant association in 15 of the 16 items questioned. The most significant disagreements (p < 0.001) were: “Firing a firearm” and “Entering a swamp or river to look for or chase someone”. Regarding health conditions, 2 was significantly associated with the six items questioned. The most significant disagreement was about the stress level, which was considered high in 46% of firefighters, 38% of police officers, and 35% of guards. Low back pain was present in 51% of firefighters, 44% of police officers and 39% of guards. There was also a significant association in the six items regarding working conditions. The most considerable disagreement was about the workplace, which was considered inadequate by 33% of guards, 26% of firefighters, and 18% of police officers. Furthermore, the salary was deemed insufficient by 87% of guards, 74% of firefighters and 65% of police officers. Conclusions: Although the guards carries out public security and social defense activities, disagreements were found at several points in the investigation compared to the police officers and firefighters. The results obtained are a rich source of information for managers and researchers in public security.Keywords: Tactical Personnel Health. Professional Stress. Low Back Pain. Sleep. Shift Work.